Neurobehavioral factors associated with referral for learning problems in a community sample: evidence for an adaptational model for learning disorders. - Waber DP; Weiler MD; Forbes PW; Bernstein JH; Bellinger DC; Rappaport L (Journal of Learning Disabilities)
We evaluated community general education (CGE; n = 178), community special education (CSE; n = 30) and hospital-referred (HR, n = 145) children (ages 7-6 to 11-11) prospectively over a 2-year period. During this period, 17 CGE children were referred for evaluation (community referred; CR). Prior to referral, CR children performed more poorly than community-nonreferred (CNR) children on cognitive ability, academic achievement, attention problems, and information processing. CR group performance was equivalent to that of CSE and HR groups, but HR children showed poorer academic achievement. Referred children performed more poorly on all measures than nonreferred, whether they met formal diagnostic criteria for a learning disorder or not. Learning disorders may be better conceptualized as a context-dependent problem of functional adaptation than as a disability analogous to physical disabilities, raising questions about the validity of using psychometric test scores as the criterion for identification.